2012
DOI: 10.1093/hmg/dds224
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of coronary artery disease associated variation on chromosome 9p21 in vascular smooth muscle cells

Abstract: Variation on chromosome 9p21 is associated with risk of coronary artery disease (CAD). This genomic region contains the CDKN2A and CDKN2B genes which encode the cell cycle regulators p16(INK4a), p14(ARF) and p15(INK4b) and the ANRIL gene which encodes a non-coding RNA. Vascular smooth muscle cell (VSMC) proliferation plays an important role in the pathogenesis of atherosclerosis which causes CAD. We ascertained whether 9p21 genotype had an influence on CDKN2A/CDKN2B/ANRIL expression levels in VSMCs, VSMC proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 36 publications
3
124
1
3
Order By: Relevance
“…CDKN2A/B has not only been demonstrated to be associated with T2DM (Cauchi et al, 2008;Scott et al, 2007), but also with atherosclerosis (Motterle et al, 2012). None of these, however, was associated with IA in our study.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…CDKN2A/B has not only been demonstrated to be associated with T2DM (Cauchi et al, 2008;Scott et al, 2007), but also with atherosclerosis (Motterle et al, 2012). None of these, however, was associated with IA in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…CDKN2A/B has not only been associated with T2DM (Scott et al, 2007;Cauchi et al, 2008), but also with atherosclerosis (Motterle et al, 2012). TCF7L2, the transcription factor 7-like 2 gene, has been associated with T2DM, and its variants have been shown to confer T2DM risk (Scott et al, 2007;Sladek et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These identified variants could be considered as predisposing factors for cancers through creating a disabled form of mentioned tumor suppressor genes. Also SNPs located in the ANRIL locus have been reported to be strongly associated with increased susceptibility to various human diseases (18)(19)(20). It is indicated that SNPs located in the 9p21 region can change the expression level of the 3 adjacent genes CDKN2A, CDKN2B, and ANRIL up to 2-fold but the expression level of CDKN2B, and ANRIL were changed in an opposite way that referred to the antisense regulating role of ANRIL on the expression of the CDKN2B gene that pointed at the consequence of modulations in ANRIL expression that increase the risk of developing human disease (20).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies identified antisense noncoding RNA in the INK4 locus (ANRIL), a lncRNA expressed in VSMC, which was able to regulate CDKN2A/B expression in aortic VSMC and attenuate proliferation in atherosclerosis [64][65][66] as well as modulate inflammatory responses in coronary artery disease [67].…”
Section: Role Of Lncrnas In Vascular Remodellingmentioning
confidence: 99%